Ajaran Tasauf dalam Sastra Gending - Muh Sungaidi (Himpunan Peminat Ilmu-Ilmu Ushuluddin (HIPIUS), 2014)
The book (Serat) Sastra Gending is written by Sultan Agung, and contains two vast topics, i.e. theology and sufism. In terms of theology, Sultan Agung describes that theology is a unity of three elements configurating equilateral triangularity, in which God is located in the peak point, while other two points are in the beneath resided by human beings and universe. Whereas in terms of sufism (tasauf), as represented in the socio-religious condition of Jawa inland-people (Pajang-Islamic Mataram), Sultan Agung uses it as ethical and behavioral teachings. As an adherent of Shaykh Siti Jenar’s mysticism—and all at once his admission as a student of Sunan Kalijaga—Sultan Agung has formed a different tasauf concept. He, seen from Sastra Gending, succeeded to create synthesis in between normative devotion based on sharī‘a and tasauf. In one hand, he teaches the importance of sharī‘a as basis of tasauf (i.e. Sunnite tasauf); on the other, he also endorses the existence of philosophical tasauf with ḥulūl doctrine as one of the concepts.